2022
DOI: 10.1098/rspa.2021.0904
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble-SINDy: Robust sparse model discovery in the low-data, high-noise limit, with active learning and control

Abstract: Sparse model identification enables the discovery of nonlinear dynamical systems purely from data; however, this approach is sensitive to noise, especially in the low-data limit. In this work, we leverage the statistical approach of bootstrap aggregating (bagging) to robustify the sparse identification of the nonlinear dynamics (SINDy) algorithm. First, an ensemble of SINDy models is identified from subsets of limited and noisy data. The aggregate model statistics are then used to produce inclusion probabiliti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(100 citation statements)
references
References 87 publications
2
95
3
Order By: Relevance
“…Currently there are several emerging methods that allow for a broader viewpoint of building models directly from noisy data, recent innovations in DMD, for instance, have shown that statistical bagging methods can greatly increase the discovery of robust, accurate and stable linear models (Askham & Kutz, 2018; Sashidhar & Kutz, 2021). This has motivated the use of ensembling and bagging for building nonlinear, parsimonious dynamic models (Fasel et al., 2022; Hirsh et al., 2021). Such non‐linear dynamic models have the potential to unravel the contemporaneously overlapping information that are representative of AE or seismic events generated by different processes, for example, fracturing, slip on faults, chemical reactions, or the various phenomena that transpire during fluid movement through porous media.…”
Section: Discussionmentioning
confidence: 99%
“…Currently there are several emerging methods that allow for a broader viewpoint of building models directly from noisy data, recent innovations in DMD, for instance, have shown that statistical bagging methods can greatly increase the discovery of robust, accurate and stable linear models (Askham & Kutz, 2018; Sashidhar & Kutz, 2021). This has motivated the use of ensembling and bagging for building nonlinear, parsimonious dynamic models (Fasel et al., 2022; Hirsh et al., 2021). Such non‐linear dynamic models have the potential to unravel the contemporaneously overlapping information that are representative of AE or seismic events generated by different processes, for example, fracturing, slip on faults, chemical reactions, or the various phenomena that transpire during fluid movement through porous media.…”
Section: Discussionmentioning
confidence: 99%
“…But the question remains as to whether the algorithm will converge to the correct sparse solution. A remedy to this can be to use the rationale of an ensemble, proposed in [43] to build an ensemble of sparse models. It can provide statistical quantities for the feature candidates in the dictionary.…”
Section: Outputmentioning
confidence: 99%
“…The former intrinsically produces models with high bias and low variance, while the latter produces models with low bias and high variance. Such pooling strategies have been recently explored in [22], where it is found that identifying a single model can be improved by pooling models learned from subsets of the data. However, this has not been extended to classifying the data itself into species, and finding a model for each species.…”
Section: Directional Interaction Forcesmentioning
confidence: 99%
“…where |C| denotes the number of elements in C. This ensemble average preserves the force modes that identify C. As explored in [22], in some cases it may be more appropriate to use the coefficient median, or take a weighted average. We leave these for future work.…”
Section: Aggregate Having Formed the Model Clusters Cmentioning
confidence: 99%